Penerapan Good Corporate Governance; Dampaknya terhadap Prediksi Financial Distress pada Sektor Perdagangan, Jasa dan Investasi - Wijayana, Debora (Business Accounting Review, 2013)
This study aimed to know whether the level of implementation of Good Corporate Governance (GCG score) capable to predict the posibility of a firm experiencing financial distress. In this study, the implementation of good corporate governance was proxied by the Board of Commissioners, the Audit Committee, and ownership structure. This study also considered other variables as control variables, namely Net Profit Margin (NPM), Current Ratio (CR), and Debt to Asset Ratio (DTA). The samples used in this study were trade, service and investment companies listed in the Indonesia Stock Exchange with certain criteria. The hypothesis in this study was tested by using binary logistic regression analysis with three prediction models for 1 year, 2 years, and 3 years before the company declared as a financial distress firm or non-financial distress firm. The results of this study stated consistently that GCG score in the three models was not significant in predicting the posibility of a firm experiencing financial distress. Meanwhile, the DTA had consistently expressed significantly in all the three models; NPM expressed significantly in model 1 and 2; while CR was only expressed significantly in model 1. The results also stated that model 2 had the greatest prediction accuracy.